POLIO ERADICATION IN INDIA: NEW INITIATIVES IN SANITATION - Sukla, Pradeep; Sharma, Karun Dev; Rana, Manish; Zaidi, Syed Hasan Nawaz (Indian Journal of Community Health, 2013)
Abstract: Polio eradication continues to be a priority in the South-East Asia Region. For developing countries, considering that the practice of open defecation and fecal contamination of drinking water easily precipitates virus transmissions, the eradication of polio called for rounds after rounds of campaign. In the districts of western Uttar Pradesh (UP), in India, which continues to be polio endemic, key challenge is the low levels of sanitation and personal hygiene. The residents of polio endemic areas are now reluctant to frequent pulse polio immunization rounds and are using these rounds to raise their voice against chronic apathy to providing the basic amenities such as adequate sanitation facilities. Newer initiatives such as Urban Sanitation and Hygiene Action (USHA) Project, in western UP and “107 block” campaign launched in UP and Bihar aiming to improve sanitation, water quality and routine immunizations in the high risk polio endemic administrative blocks have the potential to significantly strengthen eradication efforts, especially in high risk areas for wild poliovirus transmission in North India.